Analisis Implikatur dalam Meme Populer pada Akun Instagram Remaja Arab - Yasmin Azizi; Hetti Waluati Triana; Arwemi Arwemi (Diwan: Jurnal Bahasa dan Sastra Arab, 2019)
This study aims to describe the implicature types used by the memes creator on the Instagram account of I.Q Shabab to deliver messages to his followers (readers). This research was a qualitative descriptive study. The data were collected by using a literary data collection technique, which collects data that is coherent with the object of the intended discussion. During the data collection process, researchers took notes, which include descriptive notes and reflective notes. The result showed that there are 3 data used general conversational implicature, 10 data used special conversation implicature, and 4 data used a scalar implicature.